Comparison of instep kicking between preferred and non-preferred leg in young football players - Bjelica, D.; Popovic, S.; Petkovic, J. (Montenegrin Journal of Sports Science and Medicine, 2013)
This research was aimed at gaining relevant knowledge about important differences with respect to compare accuracy of instep kicking between preferred and non-preferred leg depending on the different intensity (optimal and maximal) in a resting state, and in a state of fatigue. The sample included 20 respondents whose characteristics were age (yrs) 16.7±0.47, height (cm) 178.91±4.26, and body weight (kg) 71.52±5.13. The sample of variables contained eight measures that defined accuracy of instep kicking by preferred and non-preferred leg in various occasions: with optimal and maximal intensities and in a resting state and a state of fatigue respectively. The results of the measuring were analyzed by means of a statistical procedure labeled a significance test of two arithmetic means conducted on independent samples or popularly known a t-test. In comparison of accuracy between preferred and non-preferred leg in a resting state with optimal and maximal intensity, as it was expected there were significant differences as well as in a state of fatigue with optimal intensity, all in favor of preferred leg. While the football instep kicking significant differences between preferred and non-preferred leg in a state of fatigue with maximal intensity were not noticable. The current findings clearly demonstrated that the young football players have much more uniformed legs at the expense of accuracy when fatigued and kick the ball with the maximal intensity. It means a state of fatigue can affect the tested accuracy of instep kicking with the maximal intensity.